Seismic dispersion and attenuation in Mancos shale – laboratory measurements. (23rd December 2020) - Mikhaltsevitch, V.; Lebedev, M.; Pervukhina, M.; Gurevich, B.
ABSTRACT: We present the results of a low‐frequency study of Mancos shale, where we first elaborate a stress–strain methodology of laboratory low‐frequency experiments to estimate the elastic moduli of shales, and then apply this methodology to investigate the influence of partial water saturation on the elastic and anelastic parameters, velocities and P‐wave anisotropy of Mancos shale. We also analyse the applicability of the anisotropic Gassmann theory for predictions of the stiffness tensor components of the water‐saturated shale with non‐expandable clay content presented in our case by illite (33%) and chamosite (9.1%) minerals. The effect of water saturation was studied using two samples drilled in vertical and parallel directions to the formation bedding. The experiments were carried out at a confining pressure of 10 MPa in the frequency range from 0.1 to 100 Hz. Prior to measurements, the samples were saturated in desiccators at six different values of relative humidity ranging from 9% to 97.5%. The results of our study demonstrate a reduction of Young's modulus and P‐wave anisotropy with saturation accompanied by a decrease in shear stiffnesses. The latter indicates the inapplicability of the anisotropic Gassmann theory to Mancos shale. Our measurements of attenuation carried out on the vertical and horizontal samples saturated at a relative humidity of 97.5% revealed prominent attenuation peaks associated with partial saturation. We showed that the measurement results of the attenuation and Young's modulus dispersion are consistent with the causality principle presented by the Kramers–Kronig relations.